Intake Fractions for Volatile Organic Compounds in Two Occupied California Residences - Lunderberg, David M; Liu, YingJun; Misztal, Pawel K.; Arata, Caleb; Tian, Yilin; Kristensen, Kasper; Nazaroff, William W.; Goldstein, Allen H (Environmental Science & Technology Letters, 2021)
Experimental estimates of residential intake fractions for indoor volatile organic compound (VOC) releases are scarce. We evaluated individual intake fractions (iFi, mass inhaled by an individual per unit mass emitted) using approximately five months of time-resolved VOC measurements acquired at two residences. First, we directly estimated iFi using inert tracer gases that were released at fixed rates. Tracer gas iFi values were generally consistent between occupants and comparable across seasons. Furthermore, iFi for sources released on different floors of a residence were statistically indistinguishable, suggesting that source location within the living space was not strongly influential. Emissions from living space sources (iFi ∼ 0.3% = 3000 ppm) contributed to occupant exposures at rates 2–4 times higher than crawl space sources (iFi ∼ 1000 ppm) and greater than 40 times higher than attic sources (iFi < ∼70 ppm). Second, we indirectly estimated iFi for 251 VOCs using net emission rates estimated by indoor–outdoor material balance. Although emission patterns varied between compounds, all VOC-specific iFi estimates were clustered near the values of the living space tracer gases. These experimental observations substantiate the theoretical expectation that iFi values are largely independent of analyte characteristics, a useful simplification for exposure assessments.